Landscape plantarum in Islamic built environment - Othman, Rashidi; Mat Ali, Qurratu Aini; Mohd Hatta, Farah Ayuni; Ramya, Razanah; Abu Yazid, Anis Fatihah (IIUM Press, 2016)
This book is an attempt to compile information theories and clear illustration on trees which is almost 100 species of trees with different families. It highlights the trees anatomy, texture, characteristics, color and structure as well as explains of trees behavior. The preparation of the book grew out of the need to elaborate to the students about plant materials and selection. Most of these students will use it as a text book especially in landscape architecture field. Other background who will benefits from this book include an architect, planner, owner of nursery, researcher and public people in understanding deeply about trees characteristics and behavior. There is no doubt that even people with some basic of knowledge about trees will be able to make use this book as guide in landscape design project and identification of trees on nursery before transfer to site project.